The Differential Effects of the Algorithm and Proportional Reasoning Approaches on Senior High School Students’ Understanding of Titrimetric Analysis - Baah, Kennedy Ameyaw; Boachie, Solomon; Quansah, Francis; Danquah, Joan (International Journal of Scientific Research and Management (IJSRM), 2019)
This study evaluated The Differential Effects of Algorithm and Proportional Reasoning Approaches on Senior High School Students’ Understanding of Titrimetric Analysis in Berekum Presbyterian Senior High School in the Brong Ahafo Region. The target population was the science students in the school. The accessible population consisted of science one and science two final year elective chemistry students. Quasi-experimental design was used for this study. In this design the researcher used a questionnaire and test to solicit information on students’ understanding on the Effects of Proportional and Algorithm Reasoning Approaches. Purposive sampling technique was used to select 30 students for the research. Science A students formed the experimental group and were taught using algorithm approach while the science B students comprised the control group and were taught using the proportional reasoning approach. There was no interaction between the control group and the experimental group. Difference in performance in pre-test and post-test, the analysis of the study imply that students exposed to algorithm instructional approach to the teaching and learning in titrimetric analysis performed statistically better at significant level (p-value = 0.000 at a=0.05). Students in the experimental group (algorithm approach) performance were better in post-test than the post-test of students in the control group (proportional reasoning). The Hake Gain was then used to calculate for students understanding in titrimetric analysis using algorithm instructional approach in teaching and learning of titrimetric analysis. The gain 0.46 (SD = 0.132) achieved fell within the range i.e. 0.36< 〈 g〉